2005
DOI: 10.1080/02699050400025299
|View full text |Cite
|
Sign up to set email alerts
|

Children and young adults in a prolonged unconscious state due to severe brain injury: Outcome after an early intensive neurorehabilitation programme

Abstract: Almost two-thirds of the patients reached full consciousness. LOC at admission, aetiology and interval since injury were found to be significant prognostic factors. Traumatic patients had a much better outcome than non-traumatic patients. A comparison with earlier outcome studies showed a more favourable outcome than expected. It is argued that a multi-centre study is needed to confirm possible effects of EINP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 41 publications
7
51
2
1
Order By: Relevance
“…With an average of four months and a mean of two and a half months for individuals arriving from acute care, and an average of 11 months and mean of seven months for individuals arriving from elsewhere, our findings are notably longer than that reported for the USA and European countries [9][10][11][12]38] and instead are similar to those of lower-income countries [13]. Our values also differ notably from other Saudi Arabian research which has shown mean acute care LOS to be between 50 [14] and 94 days [8].…”
Section: Time From Injury To Rehabilitation Admissioncontrasting
confidence: 53%
See 1 more Smart Citation
“…With an average of four months and a mean of two and a half months for individuals arriving from acute care, and an average of 11 months and mean of seven months for individuals arriving from elsewhere, our findings are notably longer than that reported for the USA and European countries [9][10][11][12]38] and instead are similar to those of lower-income countries [13]. Our values also differ notably from other Saudi Arabian research which has shown mean acute care LOS to be between 50 [14] and 94 days [8].…”
Section: Time From Injury To Rehabilitation Admissioncontrasting
confidence: 53%
“…Two US studies using data from the NIDRR TBI Model Systems National Data Base in the 1990s reported acute care length of stay, which preceded rehabilitation admission, to vary from 12±8 days for relatively mild TBI to 44±28 days for extremely severe TBI [9] and from 24±23 days to 33±36 days for younger and older individuals, respectively [10]. In a study involving children and young adults in the Netherlands, the interval between injury and admission was significantly longer for patients admitted before the introduction of an "Early Intensive Neurorehabilitation Program" (82±38 days) compared to the patients admitted after programme introduction (64±32 days) [11]. In a survey of 18 rehabilitation centres in France, time between injury and admission was 1 to 4 weeks [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that functional outcome is related to vigilance level at discharge [18]. This may be explained by the fact that recovery of consciousness is a prerequisite for recovery of function [17].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the regain of consciousness and the ability to follow commands were considered to be important early prognostic parameters since they are a prerequisite for successful rehabilitation [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…All patients involved in the Early Intensive Neurorehabilitation Programme (EINP) were children and young adults. They were in a VS/UWS or MCS as a result of severe brain damage acquired between November 2002 and January 2004 [15]. This treatment aims to maximize patient's ability to process and respond to stimuli and information of increasing variety and complexity.…”
Section: Participantsmentioning
confidence: 99%